Fall risk among older adults residing in Bharatpur, Chitwan, Nepal - Limbu, Jogmaya; Poudyal, Sunita (Journal of Chitwan Medical College, 2020)
Background: Falls in older people is a common serious health problem that has profound impact on overall health and quality of life of older people. The aim of this study was to assess the fall risk among older adults. Methods: The descriptive cross-sectional study was carried out among older adults residing in Bharatpur, Chitwan. A total of 98 older adults were selected by using simple random sampling technique. The data were collected by using structured interview schedule and fall risk was assessed by Timed Up and Go (TUG) test. Data were collected from 23rd June, 2019 to 7th July, 2019. Obtained data were analyzed using descriptive and inferential statistics. Results: The study findings revealed that more than half (60.2%) of the older adults were from the age group of ≤79 years, male (63.3%) and almost half (50%) were illiterate. Nearly all (96.9%) older adults were living with their family however, 50% were undernourished (BMI- <22.9). Majorities (66.3%) were suffering from chronic diseases and had been taking medicine. Majority of older adults reported vision problem (64.3%) and hearing problem (60.2%). However, only 8.2% reported history of fall within last 6-12 months. More than half (59.2%) of the older adults had high risk of fall and found significant association with age (p=0.039) and vision problem (p=0.043). Conclusions: More than half of the older adults are in risk of falls. Therefore, more emphasis should be given in screening the older people for fall risk factors as preventive measures.